Spontaneous Conception and Favorable Obstetric Outcome in a Patient with PCOS and Class II Obesity: A Case Report - Melisa Indah Mustikasari; Manggala Pasca Wardhana; Anin Indriani; Alexander Tikara Sugondo; Made Chindy Dwiyanti Marheni Putri (Health Dynamics, 2025)
Polycystic ovary syndrome (PCOS) and obesity are prevalent conditions that independently impair fertility and increase the risk of adverse pregnancy outcomes. When coexisting, they present compounded challenges for conception and pregnancy management. We report a case of a 27-year-old primigravida with PCOS and class II obesity who achieved spontaneous conception after three years of infertility and multiple failed assisted reproductive attempts. Preconception lifestyle modifications and medical management improved insulin sensitivity and restored ovulatory function. Despite being categorized as a high-risk pregnancy, the antenatal course was unremarkable, with appropriate fetal growth and no major maternal or neonatal complications. Vaginal delivery occurred at term, resulting in a healthy newborn. This case highlights the potential for favorable reproductive and obstetric outcomes in women with PCOS and obesity through early diagnosis, lifestyle intervention, and meticulous prenatal care. It underscores the importance of individualized and multidisciplinary management strategies in optimizing maternal and fetal health. Spontaneous conception and favorable pregnancy outcomes are achievable in women with PCOS and obesity through comprehensive care. Early intervention and tailored monitoring play a crucial role in mitigating risks associated with these conditions.